Development and analytical validation of a novel bioavailable 25-hydroxyvitamin D assay. - Anders H Berg (Public Library of Science (PLoS), 2021)
Background Bioavailable 25-hydroxyvitamin D (25OHD) may be a better indicator of vitamin D sufficiency than total 25OHD. This report describes a novel assay for measuring serum bioavailable 25OHD. Methods We developed an assay for 25OHD % bioavailability based on competitive binding of 25OHD tracer between vitamin D-binding protein (DBP)-coated affinity chromatography beads and serum DBP. Bioavailable 25OHD, total 25OHD, albumin, and DBP protein concentrations were measured in 89 samples from hospitalized patients and 42 healthy controls to determine how the DBP binding assay responds to differences in concentrations of DBP and compares to calculated bioavailable 25OHD values. Results DBP binding assay showed a linear relationship between DBP-bound 25OHD tracer recovered from bead supernatant and DBP calibrator concentrations (y = 0.0017x +0.731, R2 = 0.9961, p<0.001). Inversion of this relationship allowed interpolation of DBP binding equivalents based upon 25OHD tracer recovered. The relationship between DBP binding equivalents and % bioavailability fits a non-linear curve, allowing calculation of % bioavailable 25OHD from DBP binding equivalents (y = 10.625x-0.817, R2 = 0.9961, p<0.001). In hospitalized patient samples, there were linear relationships between DBP protein concentrations and DBP binding equivalents (y = 0.7905x + 59.82, R2 = 0.8597, p<0.001), between measured vs. calculated % bioavailability (y = 0.9528 + 0.0357, R2 = 0.7200, p<0.001), and between absolute concentrations of measured vs. calculated bioavailable 25OHD (y = 1.2403 + 0.1221, R2 = 0.8913, p<0.001). Conclusions The DBP-binding assay for bioavailable 25OHD shows expected changes in 25OHD % bioavailability in response to changes in DBP concentrations and concordance with calculated bioavailable 25OHD concentrations.